Nutrition status of the elderly population having dental problem in the selected community. - Gaire,Bipula (2019)
ABSTRACT: Background: Good nutrition is the foundation for a healthy life. Malnutrition is associated with higher rates of morbidity and mortality as well as increased health care expenditures, and prolonged hospital stays. Elderly People are uniquely susceptible to malnutrition due to the association of aging with various factors that influence nutritional status. Therefore we need to prepare for the obligation to address the specific social, psychological, economic, and particularly health needs of this elderly population. Objectives: The objectives of the study was to assess the nutritional status of the elderly population having dental problem in ward no. 29 Harisiddhi, Lalitpur. Methodology: A community based cross sectional descriptive study was undertaken at, ward no. 29 Harisiddhi, Lalitpur with one hundred fifty (N=150) elderly people by using systematic random sampling method. The MNA tool was utilized for interviewing the elderly people. Results: The main findings of this study revealed that 60% of the elderly people were at risk of malnutrition, only 22% had normal nutritional status and 18% of the respondents were malnourished. The average BMI of the elderly people was 27.1 kg/m2.There was significant association between age, educational Status, types of family, income source, type of dental problem and nutritional status of the respondents. Conclusions: More than half of the elderly people are at risk of malnutrition and only few have normal nutritional status so nutritional counselling and dental health program should be conducted among the elderly people focusing on the importance of balanced diet, activity and dental health for maintaining the nutritional status within their motivation and energy level. Keywords: Nutritional Status, Dental Problems, Elderly People.